Pemasaran Politik Lilis Nurlia dan Eka Widyani Latief Pada Pemilu 2019 di Kota Bekasi - Setiyani, Wiji (Politeia: Jurnal Ilmu Politik, 2023)
The 2019 election is a new history because the elections were held simultaneously. This creates a challenge for the legislative candidates on how to inform and convince the public. The number of elected female candidates is still small compared to the male candidates. Hence the need for political marketing, to be able to win the election. Political marketing is a candidate's strategy to win the election. This paper aims to explain the political marketing of Lilis Nurlia and Eka Widyani Latief in the 2019 election in Bekasi City by using the political marketing theory of Philip B. Niffenegger. The research method used is qualitative research with a case study approach to obtain an overview of the phenomenon from the political marketing experience of Lilis Nurlia and Eka Widyani Latief. The result is that Lilis Nurlia and Eka Widyani Latief can implement political marketing properly according to product, price, promotion, and place. It becomes interesting when Lilis Nurlia uses a success team in facing the 2019 election, while Eka Widyani Latief does not use a success team. Lilis Nurlia served in 2014 and Eka Widyani Latief served in the 2004 and 2009 elections in Bekasi City. This means that Lilis Nurlia and Eka Widyani are one step ahead of the other candidates.